Physiological and Comparative Evidence Fails to Confirm an Adaptive Role for Aging in Evolution - A. Cohen, Alan (Current Aging Science, 2015)
The longstanding debate about whether aging may have evolved for some adaptive reason is generally considered to pit evolutionary theory against empirical observations consistent with aging as a programmed aspect of organismal biology, in particular conserved aging genes. Here I argue that the empirical evidence on aging mechanisms does not support a view of aging as a programmed phenomenon, but rather supports a view of aging as the dysregulation of complex networks that maintain organismal homeostasis. The appearance of programming is due largely to the inadvertent activation of existing pathways during the process of dysregulation. It is argued that aging differs markedly from known programmed biological phenomena such as apoptosis in that it is (a) very heterogeneous in how it proceeds, and (b) much slower than it would need to be. Furthermore, the taxonomic distribution of aging across species does not support any proposed adaptive theories of aging, which would predict that aging rate would vary on a finer taxonomic scale depending on factors such as population density. Thus, while there are problems with the longstanding non-adaptive paradigm, current evidence does not support the notion that aging is programmed or that it may have evolved for adaptive reasons.
Keywords: Adaptation